Overachievers and underachievers at the last three Rugby World Cups - Stefani, R. (Significance, 2016)
The World Rugby rating system proved to be very accurate in that the higher-rated teams, pre-World Cup, won 85.2% of 142 non-tied matches. Nations with losing records were able to pull off upset wins (top panel of Table 1) while dominant nations still had a few upset losses (bottom panel of Table 2). Argentina rose to the demands of the Rugby World Cup by pulling off five upset wins with no upset losses. France was the biggest underachiever with four upset losses and only one upset win. The African content was the most predicable. Namibia, Portugal, Russia and Uruguay met expectations by losing all 24 matches, combined. New Zealand, South Africa, Australia and Ireland also lived up to expectations. The Southern Hemisphere dominated over the Northern Hemisphere in wins versus losses and in overachievement. Let`s reconvene this study in Japan in 2019 where the Brave Blossoms will be the hosts. Look to the World Rugby ratings pre-World Cup to see who is likely to win matches.